2015
DOI: 10.1111/jth.12982
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of retinal vein occlusion: the Gutenberg Health Study

Abstract: Summary. Objective: To determine the age-and sex-specific prevalence and determinants of retinal vein occlusions (RVOs) in a large population-based German cohort. Methods: The investigation included 15 010 participants (aged 35-74 years) from the Gutenberg Health Study. We determined the prevalence of RVO (central retinal vein occlusion [CRVO] and branch retinal vein occlusion [BRVO]) for the local population by assessing fundus photographs of 12 954 (86.3%; 49.8% women and 50.2% men) participants. Further, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
65
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 65 publications
9
65
3
4
Order By: Relevance
“…6,7 BRVO typically occurs in the middle aged and elderly patients (>50 yrs) with male predominance. [8][9][10][11][12] The predominant risk factors are cardiovascular diseases, diabetes, primary glaucoma and hyperlipidaemia. [7][8][9][10][11] Hypertension being the predominant risk factor among cardiovascular diseases.…”
mentioning
confidence: 99%
“…6,7 BRVO typically occurs in the middle aged and elderly patients (>50 yrs) with male predominance. [8][9][10][11][12] The predominant risk factors are cardiovascular diseases, diabetes, primary glaucoma and hyperlipidaemia. [7][8][9][10][11] Hypertension being the predominant risk factor among cardiovascular diseases.…”
mentioning
confidence: 99%
“…The prevalence of RVO by age could not be investigated in more detail because of a lack of reported data. Three of the 4 studies included in the analysis also reported the observed proportion of central RVO [32, 36], ranging from 15 to 25%. Prevalence of bilateral RVO was only reported in the GHS in 3.4% of participants (2 subjects with branch RVO) [36].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of RVO in Europe ranged from 0.5% (Gutenberg Health Study [GHS], Germany, mean age 55.0 years) [36] to 1.1% (Antioxydants, Lipides Essentiels, Nutrition et Maladies Oculaires [ALIENOR] study, France, mean age 79.8 years) [35]. The prevalence of RVO by age could not be investigated in more detail because of a lack of reported data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations